High resolution fiber optic ph sensor with indicator dye immobilized in polyaniline cladding / Norliza Othman - Othman, Norliza (2017)
Optical pH sensors offer a promising alternative over the existence electrochemical and other pH sensors due to the ability to achieve high performance, electrical passive operation, simplicity and price effectiveness. Recently, significant research efforts have been devoted to pH sensors for the detection of pH variation in high resolution and pH change over a small range. It becomes important to consider ways to improve the sensitivity of the sensor by improving both the properties of the material and simple method of sensor fabrication. Effort has been put in studying the fabrication and the sensitivity of active thin film towards pH range in physiological applications. Most optical sensors consist of an indicator which is immobilized in a glass or polymer matrix. In this research, polyaniline act as a sol - gel matrix to support pH sensitive indicator molecules which are bromothymol blue and phenol red. Polyaniline has been found to be versatile functional material which is the most suitable organic material to act as a matrix in liquid and has the capability to sense pH changes optically. The combined optical properties of polyaniline and bromothymol blue or phenol red will enhance the sensitivity of the sensor. The sensing capabilities of the device in term of its optical absorption intensity with different pH values were explored. Besides that, simpler and low-cost method was adopted and developed. The two indicators were doped separately in polyaniline sol-gel and deposited by dip coating on planar substrate for process optimization before deposited as cladding on a portion of fiber optic. Sensor performance were observed to be affected by several process parameters including concentration of dye, number of deposition layers, drying duration, withdrawal speed and length of re-cladded portion on the fiber.